Exploring the pattern of Road Traffic Accidents over the highways: A study from western Uttar Pradesh, India - Urfi; Khalique, Najam; Ahmad, Anees (Indian Journal of Community Health, 2024)
Background: By the year 2019, road traffic accidents (RTAs) became the leading cause of death among children and young individuals between the ages of 5 and 29 years. Aim & Objective: To explore the pattern and severity of road traffic injuries (RTIs) over the national highways and connecting bypass roads in the district Aligarh of Uttar Pradesh. Methods and Material: The study included all the individuals who met RTA over the selected stretches of roads and availed treatment at the identified hospitals over these roads. Results: The study finally had 1126 patients. The mean age was 31.89+13.81 years. 937 (83.2%) were males and 189 (16.8%) were females. The most common mode of transport used was two-wheelers (74.40%) followed by pedestrians (11.20%). More than half of the patients were driving the vehicles. 682 (60.60%) and 301 (26.70%) RTAs were recorded on NH91 and NH93 respectively. More than 95% of RTAs recorded had moderate to severe injuries. The severity of RTIs varied significantly with the type of transport and road user, the time and place of the crash, the collision type, and the body part primarily injured. Conclusions: Young males driving motorized two-wheelers are most vulnerable to moderate to severe RTIs.